Effect of Gestational Diabetes on Serum Leptin during Pregnancy and Postpartum Period - Jazib Andleeb; Faiza Mehboob; Sana Javaid; Mudassar Ali; Muhammad Imran Khan; Qurat-ul-Ain (The International Journal of Frontier Sciences, 2024)
Background: Gestational diabetes mellitus (GDM) is associated with marked increase in insulin resistance. The objective of study is to determine the relation of gestational diabetes with serum leptin and serum insulin levels during pregnancy and postpartum period.